Chemogenetic Recruitment of Specific Interneurons Suppresses Seizure Activity - Cǎlin, Alexandru; Stancu, Mihai; Zagrean, Ana-Maria; Jefferys, John G. R.; Ilie, Andrei S.; Akerman, Colin J. (Frontiers in Cellular Neuroscience, 2018)
Current anti-epileptic medications that boost synaptic inhibition are effective in reducing several types of epileptic seizure activity. Nevertheless, these drugs can generate significant side-effects and even paradoxical responses due to the broad nature of their action. Recently developed chemogenetic techniques provide the opportunity to pharmacologically recruit endogenous inhibitory mechanisms in a selective and circuit-specific manner. Here we use chemogenetics to assess the potential of supressing epileptiform activity by enhancing the synaptic output from three major interneuron populations in the rodent hippocampus: parvalbumin (PV), somatostatin (SST) and vasoactive intestinal peptide (VIP) expressing interneurons. To target different neuronal populations, promoter-specific cre-recombinase mice were combined with viral-mediated delivery of chemogenetic constructs. Targeted electrophysiological recordings were then conducted in an in vitro model of chronic, drug-resistant epilepsy. In addition, behavioural video-scoring was performed in an in vivo model of acutely triggered seizure activity. Pre-synaptic and post-synaptic whole cell recordings in brain slices revealed that each of the three interneuron types increase their firing rate and synaptic output following chemogenetic activation. However, the interneuron populations exhibited different effects on epileptiform discharges. Recruiting VIP interneurons did not change the total duration of epileptiform discharges. In contrast, recruiting SST or PV interneurons produced robust suppression of epileptiform synchronisation. PV interneurons exhibited the strongest effect per cell, eliciting at least a five-fold greater reduction in epileptiform activity than the other cell types. Consistent with this, we found that in vivo chemogenetic recruitment of PV interneurons suppressed convulsive behaviours by more than 80%. Our findings support the idea that selective chemogenetic enhancement of inhibitory synaptic pathways offers potential as an anti-seizure strategy.